1979
DOI: 10.1056/nejm197907123010201
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative Dilatation of Coronary-Artery Stenosis

Abstract: In percutaneous transluminal coronary angioplasty, a catheter system is introduced through a systemic artery under local anesthesia to dilate a stenotic artery by controlled inflation of a distensible balloon. Over the past 18 months, we have used this technic in 50 patients. The technic was successful in 32 patients, reducing the stenosis from a mean of 84 to 34 per cent (P less than 0.001) and the coronary-pressure gradient from a mean of 58 to 19 mm Hg (P less than 0.001). Twenty-nine patients showed improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
185
0
7

Year Published

1982
1982
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,198 publications
(192 citation statements)
references
References 7 publications
0
185
0
7
Order By: Relevance
“…6 The predictive value of these angiographic findings for the occurrence of coronary vascular complications is low (< 10%). However, complicated lesions may represent a higher risk of coronary dissection or total coronary occlusion (local coronary risk).…”
Section: Discussionmentioning
confidence: 99%
“…6 The predictive value of these angiographic findings for the occurrence of coronary vascular complications is low (< 10%). However, complicated lesions may represent a higher risk of coronary dissection or total coronary occlusion (local coronary risk).…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to improve the mortality rate seen with transthoracic repair, in 1967 Diethrich et al [5] reported the first extra-anatomic SAT reconstruction; that improvement was subsequently confirmed by Crawford et al [4] who demonstrated a reduction in the mortality rate from 22% to 5.6% with extra-anatomic cervical repair. Following reports of the successful treatment of peripheral, renal and coronary artery atherosclerotic lesions by PTA [20,21], in the 1980s PTA techniques were applied to the lesions of SATs [9,10]. While these interventions were well tolerated by most patients and demonstrated acceptable perioperative efficacy and safety, long term patency and freedom from reintervention were found to be inferior to the surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In 1977, Gruentzig of Switzerland successfully executed percutaneous transluminal coronary balloon angioplasty in stricture lesion to open up a new era of coronary artery [1]. This method dilates the balloon to widen the stricture lesion, which brings about the improvement of blood flow with the dilatational balloon to expand the narrowed coronary artery.…”
Section: Introductionmentioning
confidence: 99%